Diseño y Evaluación del Desempeño de una Red de Comunicaciones para Medición Inteligente en Network Simulator–2 - Aranda, Juan Manuel (Ingeniería, 2015)
This article presents the results of design and performance evaluation of a Smart Metering or AMI network, using the Network Simulator-2. The communication network proposed combines technologies such as, PLC and HSPDA, using data concentrators (DCs) and application and transport protocols such as DLMS/COSEM and TCP/IP. The performance evaluation results shown that introducing data concentrator inside a communication network provides a superior performance compared with others that not use it. Finally, the employment of DCs on the design also extended communication coverage and reduce direct accesses to the network.